Origin and evolution of tomato production Lycopersicon esculentum in México - Tarsicio Medina Saavedra; Gabriela Arroyo Figueroa; Jorge Gustavo Dzul Cauih (Ciência Rural)
ABSTRACT: Lycopersicon esculentum known as tomato, although has an Andean origin is a contribution of Mexico to the world is, being the first agricultural product to be exported. This research aimed to review the literature in relation to the origin and evolution of the production of tomato in Mexico within the historical development of the country. In ancient times, the tomato was cultivated in milpas (open field) and chinampas (artificial islands for riparian agriculture) using sustainable methods. Spanish colonizers showed the tomato to the rest of the world and diversified its uses. In independent Mexico, haciendas and railroads integrated the different farming regions. Production decreased during the Mexican revolution, and with land reform, the milpa returned. During the Green Revolution (1970), Sinaloa stood out, with the separation of two systems, subsistence, and modern with technology programs. Biotechnological development (1990) emerged parallel to organic production. So actually with this system, we could return to more sustainable pre-Hispanic ecological principles with less environmental impact.